2003
DOI: 10.1007/s00213-002-1282-0
|View full text |Cite
|
Sign up to set email alerts
|

Baseline prolactin and L-tryptophan availability predict response to antidepressant treatment in major depression

Abstract: The PRF did not predict 6-week outcome. BLP and TRP/LNAA ratio measurement is easy and may be useful clinically. We hypothesise that failure to upregulate post-synaptic 5HT receptors in response to low 5HT availability predicts a poor response to antidepressant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
7
1
4
Order By: Relevance
“…This fi nding is consistent with a previous report showing that high BPV might predict response to nonselective tricyclic antidepressants in depressed patients with a low TRP availability [9] . As BPV are positively infl uenced by noradrenergic activity [17][18][19][20][21][22][23] , it can be hypothesized that depressed patients with comparatively high BPV have a relatively high noradrenergic function.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This fi nding is consistent with a previous report showing that high BPV might predict response to nonselective tricyclic antidepressants in depressed patients with a low TRP availability [9] . As BPV are positively infl uenced by noradrenergic activity [17][18][19][20][21][22][23] , it can be hypothesized that depressed patients with comparatively high BPV have a relatively high noradrenergic function.…”
Section: Discussionsupporting
confidence: 82%
“…Women with seasonal affective disorder seem to have lower BPV than healthy volunteers [7,8] . Recently, a relationship has been found between BPV and the ratio of L -tryptophan (TRP) to the large neutral amino acids (LNAA) in predicting 6-week outcome after antidepressant treatment with the tricyclic drugs desimipramine or clomipramine [9] . The TRP/ LNAA ratio is a measure of TRP availability (as TRP competes with LNAA for entry into the brain) [10] .…”
mentioning
confidence: 99%
“…Although we partly employed a within-subject design, and we did not observe any relationships between menstrual cycle phase and the present findings, future studies would preferably have subjects participate in the same phase. Some larger studies of basal and serotonergic challenge-induced plasma prolactin levels found no effect of phase of cycle [61] . The high correlation between the prolactin levels of both conditions, despite a treatment effect on those levels, suggests that many possible state-related confounding effects on prolactin levels exerted only limited influence, such that the prolactin measures showed sufficient reliability and stability to detect individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Ein Zusammenhang zwischen Prolaktin, der L-Tryptophan-Verfügbarkeit und antidepressiver Response wurde von Porter et al [43] beschrieben: Bei depressiven Patienten (n=104) mit vergleichsweise geringer L-Tryptophan-Verfügbarkeit fand sich eine statistisch signifikante positive Korrelation zwischen Prolaktin und Ansprechen auf eine 6-wöchige Behandlung mit trizyklischen Antidepressiva, während sich hingegen bei Patienten mit relativ hoher L-Tryptophan-Verfügbarkeit eine statistisch signifikante negative Korrelation zwischen Prolaktin und Ansprechen auf die Therapie fand. Allerdings konnten die Autoren für diese Zusammenhänge keine schlüssige Erklärung liefern.…”
Section: Plasma-markerunclassified
“…Im Gegensatz hierzu zeigte eine andere Studie (n=104) keinen Hinweis für die Hypothese, dass der Prolaktin-oder Kortisolanstieg im Fenfluramin-Stimulationstest einen Prädiktor für eine Response auf Behandlung mit Antidepressiva darstellen könnte [43]. Der große Unterschied in der Fallzahl zwischen den Studien (n=7 vs. n=104) zeigt, dass der Fenfluramin-Stimulationstest als Prädiktor für das Ansprechen auf eine antidepressive Pharmakotherapie ungeeignet erscheint.…”
Section: Neuroendokrine Stimulationstestsunclassified